XMM-Newton observations of the narrow-line Seyfert 1 galaxy IRAS 13224-3809: X-ray spectral analysis II - Jiang, Jiachen; Dauser, Thomas; Fabian, Andrew C.; Alston, William N.; Gallo, Luigi C.; Parker, Michael L.; Reynolds, Christopher S. (Monthly Notices of the Royal Astronomical Society, 2022)
Previously, we modelled the X-ray spectra of the narrow-line Seyfert 1 galaxy IRAS 13224-3809 using a disc reflection model with a fixed electron density of 10(15) cm(-3). An additional blackbody component was required to fit the soft X-ray excess below 2 keV. In this work, we analyse simultaneously five flux-resolved XMM-Newton spectra of this source comprising data collected over 2 Ms. A disc reflection model with an electron density of n(e) approximate to 10(20) cm(-3) and an iron abundance of Z(Fe) = 3.2 +/- 0.5 Z(circle dot) is used to fit the broad-band spectra of this source. No additional component is required to fit the soft excess. Our best-fitting model provides consistent measurements of black hole spin and disc inclination angle as previous models where a low disc density was assumed. In the end, we calculate the average illumination distance between the corona and the reflection region in the disc of IRAS 13224-3809 based on best-fitting density and ionization parameters, which changes from 0.43 root integral(AD)/integral(INF) r(g) in the lowest flux state to 1.71 root integral(AD)/integral(INF) r(g) in the highest flux state assuming a black hole mass of 2 x 10(6) M-circle dot. f(AD)/f(INF) is the ratio between the flux of the coronal emission that reaches the accretion disc and infinity. This ratio depends on the geometry of the coronal region in IRAS 13224-3809. So we only discuss its value based on the simple 'lamppost' model, although detailed modelling of the disc emissivity profile of IRAS 13224-3809 is required in future to reveal the exact geometry of the corona.
CRIS-Team WoS Importer:2022-06-24